Employee flourishing and moral obligation in extreme conditions - Zoogah, Baniyelme D.; Degbey, William Y.; Asiedu-Appiah, Felicity; Ogbonnaya , Chidiebere; Laker, Benjamin (Elsevier, 2025)
We extend the extant call for a flourishing perspective by examining dynamic processes involving moral obligations of organizations, work meaningfulness, organizational responsiveness, and enabling conditions and their effects on employee flourishing in four studies from an emerging economy. Through a mixed-study design, we qualitatively explore (Study 1: N = 146), perceptions of employees about the moral obligations, enabling conditions, and responsiveness of their organizations during an extreme condition. We then conduct (in Study 2) an experiment with employees (N = 63) from the Kumasi metropolis in Ghana. The results of a 2 (high and low moral obligation) × 2 (facilitative and inhibitive enabling conditions) between-subjects design show that employees in high moral obligation organizations with facilitative enabling conditions reported perceptions of better flourishing than those in the other conditions. In Study 3, cross-sectional (N = 112), we examine the mechanism and dynamics by which moral obligation influences employee flourishing. Study 4, a replication (N = 81), shows a pattern similar to that of Study 2 in the Accra metropolis in Ghana. Consistent with the human flourishing theory, we discuss implications for future research.
Keywords: Employee flourishing; Experiments; Moral obligations of organizations; Qualitative and quantitative studies; Thriving; Enabling conditions; fi=Henkilöstöjohtaminen|en=Human Resource Management|